Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure, let's find the equation of the perpendicular bisector of the given line segment step-by-step.
1. Determine the slope of the given line:
The equation of the given line is:
[tex]\[ y = -4x - 4 \][/tex]
The slope [tex]\( m \)[/tex] of this line is [tex]\(-4\)[/tex].
2. Find the negative reciprocal of the slope:
The slope of a line perpendicular to another is the negative reciprocal of the slope of the original line. So, we take the negative reciprocal of [tex]\(-4\)[/tex]:
[tex]\[ m_{\text{perpendicular}} = -\frac{1}{-4} = \frac{1}{4} \][/tex]
Thus, the slope of the perpendicular bisector is [tex]\( \frac{1}{4} \)[/tex].
3. Use the midpoint to find the y-intercept:
The midpoint of the given line segment is given as [tex]\((-1, -2)\)[/tex].
We will use the point-slope form of the equation to find the y-intercept [tex]\( b \)[/tex]. The point-slope form is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, [tex]\( (x_1, y_1) = (-1, -2) \)[/tex] and [tex]\( m = \frac{1}{4} \)[/tex].
Substituting these values in, we get:
[tex]\[ y - (-2) = \frac{1}{4}(x - (-1)) \][/tex]
[tex]\[ y + 2 = \frac{1}{4}(x + 1) \][/tex]
Next, let's solve for [tex]\( y \)[/tex]:
[tex]\[ y + 2 = \frac{1}{4}x + \frac{1}{4} \][/tex]
Subtract 2 from both sides to isolate [tex]\( y \)[/tex]:
[tex]\[ y = \frac{1}{4}x + \frac{1}{4} - 2 \][/tex]
Simplify [tex]\( \frac{1}{4} - 2 \)[/tex]:
[tex]\[ \frac{1}{4} - 2 = \frac{1}{4} - \frac{8}{4} = -\frac{7}{4} \][/tex]
So the equation of the perpendicular bisector in slope-intercept form is:
[tex]\[ y = \frac{1}{4}x - \frac{7}{4} \][/tex]
4. Compare with the given choices:
Now we look at the given choices:
[tex]\[ \text{(a) } y = -4x - 4 \][/tex]
[tex]\[ \text{(b) } y = -4x - 6 \][/tex]
[tex]\[ \text{(c) } y = \frac{1}{4}x - 4 \][/tex]
[tex]\[ \text{(d) } y = \frac{1}{4}x - 6 \][/tex]
The correct equation we derived is [tex]\( \frac{1}{4}x - \frac{7}{4} \)[/tex], and it aligns with none of the choices (we would expect choice similar to (c) or (d), but instead between the given options there is no match). As a result:
None of the given choices match the correct perpendicular bisector equation.
1. Determine the slope of the given line:
The equation of the given line is:
[tex]\[ y = -4x - 4 \][/tex]
The slope [tex]\( m \)[/tex] of this line is [tex]\(-4\)[/tex].
2. Find the negative reciprocal of the slope:
The slope of a line perpendicular to another is the negative reciprocal of the slope of the original line. So, we take the negative reciprocal of [tex]\(-4\)[/tex]:
[tex]\[ m_{\text{perpendicular}} = -\frac{1}{-4} = \frac{1}{4} \][/tex]
Thus, the slope of the perpendicular bisector is [tex]\( \frac{1}{4} \)[/tex].
3. Use the midpoint to find the y-intercept:
The midpoint of the given line segment is given as [tex]\((-1, -2)\)[/tex].
We will use the point-slope form of the equation to find the y-intercept [tex]\( b \)[/tex]. The point-slope form is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, [tex]\( (x_1, y_1) = (-1, -2) \)[/tex] and [tex]\( m = \frac{1}{4} \)[/tex].
Substituting these values in, we get:
[tex]\[ y - (-2) = \frac{1}{4}(x - (-1)) \][/tex]
[tex]\[ y + 2 = \frac{1}{4}(x + 1) \][/tex]
Next, let's solve for [tex]\( y \)[/tex]:
[tex]\[ y + 2 = \frac{1}{4}x + \frac{1}{4} \][/tex]
Subtract 2 from both sides to isolate [tex]\( y \)[/tex]:
[tex]\[ y = \frac{1}{4}x + \frac{1}{4} - 2 \][/tex]
Simplify [tex]\( \frac{1}{4} - 2 \)[/tex]:
[tex]\[ \frac{1}{4} - 2 = \frac{1}{4} - \frac{8}{4} = -\frac{7}{4} \][/tex]
So the equation of the perpendicular bisector in slope-intercept form is:
[tex]\[ y = \frac{1}{4}x - \frac{7}{4} \][/tex]
4. Compare with the given choices:
Now we look at the given choices:
[tex]\[ \text{(a) } y = -4x - 4 \][/tex]
[tex]\[ \text{(b) } y = -4x - 6 \][/tex]
[tex]\[ \text{(c) } y = \frac{1}{4}x - 4 \][/tex]
[tex]\[ \text{(d) } y = \frac{1}{4}x - 6 \][/tex]
The correct equation we derived is [tex]\( \frac{1}{4}x - \frac{7}{4} \)[/tex], and it aligns with none of the choices (we would expect choice similar to (c) or (d), but instead between the given options there is no match). As a result:
None of the given choices match the correct perpendicular bisector equation.
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.